Analysis of Strategies To Increase The Income of Fish Processing Businesses Through The Diversification of Processed Fish Products - Dinda, Mita; Dewi, Yenty Astarie; Nurani, Khadijah; Putra, Indika Juang (Peneliti.net, 2025)
This study aims to analyze income improvement strategies through diversification, covering aspects of capital conditions, technology, seasonal impacts, and strategy formulation. Method: Descriptive qualitative approach using observation and interviews with six informants, thematic analysis, and secondary data from BPS and KKP (2022–2024). The study employs a descriptive qualitative approach through observation and interviews with six informants, thematic analysis, and secondary data from BPS and KKP (2022–2024). Results show that the number of actors increased by 50%, production rose by 100%, and income grew by 84% (from IDR 44.1 million to IDR 54.2 million). Challenges: Seasonal fluctuations and limited diversification, with interest in products such as fish floss. Conclusion: Diversification supported by modern technology, sharia-based financing, and digital marketing can.